Rare events and long-run risks - Robert J. Barro; Tao Jin (American Enterprise Institute (AEI), 2016)
Rare events (RE) and long-run risks (LRR) are complementary approaches for characterizing macroeconomic variables and for understanding asset pricing. We estimate a model with RE and LRR using long-term consumption data for 42 economies. RE typically associates with major historical episodes, such as world wars and depressions and analogous country-specific events. LRR reflects gradual processes that influence long-run growth rates and volatility. A match between the model and observed average rates of return requires a coefficient of relative risk aversion, Î³, around 6. Most of the explanation for the equity premium derives from RE, although LRR makes a moderate contribution.
Keywords: A; 330; macroeconomics